Influence of solar radiation to the temperature inside a three-layer partition in winter season - Patrycja Antonik-Popiołek (Acta Scientiarum Polonorum. Architectura)
The article presents an analysis of the impact of solar radiation on the temperature changes in the external three-layer partition of a smart building. Data for analysis were taken from temperature sensors located in individual layers of the wall and from a weather station on the roof of a building. The data were recorded 24 h in 5- and 15-minute intervals. The analysis period was one month in a winter season. The purpose of the analysis was to determine the correlation between the solar radiation measured as the illuminance and the temperature inside the wall. In the analysed period of one month the correlation was very weak. Also, considering only the illuminance over 10,000 lx, the correlation was noticeable, but still very weak. The use of innovative fiber optic technology with fibre Bragg grating was proposed to avoid incorrect measurements.